Utopias and dystopias in Hungarian fiction between the two world wars - Gombos, Péter (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2024)
The study presents the appearance of two genres, utopia and dystopia, in Hungary between the two world wars. First of all, I shall briefly clarify the relationship between the genres, also justifying why they cannot be considered the same.In the next section, I shall present the historical background. This is justifiable if only because the connection between the state of the country and the style, toolkit and generally low number of novels of the genre in question is clearly visible. "The living and greatest pain of the nation inspires historical sciences and journalism, but it does not find a worthy expression in fiction." – Antal Szerb wrote (1991) about this.In the main part of my writing, I shall discuss Frigyes Karinthy's Capillaria (1921), György Kürthy's Mars (1926), Árpád Sebes' Doktor Gulliver a sarkvidéken (Doctor Gulliver in the Arctic) (1930) and Mihály Babits' Elza pilóta vagy a tökéletes társadalom (Elza pilot or the perfect society) (1933). I shall analyse the work of Karinthy and Babits in somewhat more detail - this is due to their colourfulness, elaboration and importance. In comparison with the masterpieces of the two great writers, the stories of Kürthy and Sebes seem less original and witty. At the same time, the dystopias of Babits and Karinthy are hardly comparable, since humour and irony define the atmosphere in one, while hopelessness in the other.
Keywords: dystopia; utopia; Babits Mihály; Karinthy Frigyes; Kürthy György; Sebes Árpád